Metal filling characteristics of aluminium lost foam casting - Wong, Yun Hong (2009)
In the present research, experimental investigation of flow pattern of lost foam casting has been conducted. For this project, the investigation has main objectives to investigate the effect of sprue position, pouring temperature and different pouring condition on flow pattern of aluminium lost foam casting. Casting in the shape of step five with five sections were produced mainly using a foam density of 16kg/m 3 and pouring was made at two different temperatures of 700 0c and 740 0c , three different sprue positions (middle, 'full', right and left) and two pouring conditions (vacuum and non-vacuum). The results obtained shown that pouring temperature (700 0c and 740 0c ) do not affect flow pattern for same sprue position. However, different sprue positions got different flow pattern Timing for molten aluminium to reach latest point 18 is faster for vacuum condition if compare with non vacuum condition. It is because vacuum machine has removed trapped air to make sure free flow of liquid casting material.